Implementation of Pancasila Student Profile In PKN Subject in Forming The Character of Grade V Students at Elementary School Sidodame Medan City - Pakpahan, Yasri Hannisyah (Berpusi Publishing, 2024)
This study aims to describe the implementation of the Pancasila student profile in Civic Education (PKN) learning and to determine the extent to which this implementation is able to shape the character of fifth grade students at SDN 064965 Sidodame , Medan City. The background of this study is based on the importance of integrated character education in the curriculum through strengthening the Pancasila student profile which includes six main dimensions, namely: faith and devotion to God Almighty and noble character, independence, critical reasoning, mutual cooperation, global diversity, and creativity. The approach used in this study is a qualitative approach with a descriptive method. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study indicate that the implementation of the Pancasila student profile in Civic Education learning has been carried out through intracurricular activities and student profile strengthening projects, although there are still challenges such as limited teacher understanding and lack of supporting facilities. Overall, this implementation has a positive impact on the formation of student characters who are more religious, disciplined, responsible, and have a national spirit. This research is expected to provide input for teachers and schools in optimizing the implementation of the Pancasila student profile in order to produce a generation with character and global competitiveness.